O anjo da anunciação: a definição do gênero trailer e sua reconfiguração comunicacional - Cavalcanti, Ian Costa (2015)
This dissertation's purpose is to define the trailer genre. The many faces of this object permeate its essential art and publicity duality, addressing foundations that prove this insoluble relationship, which characterizes the genre. The commercial obstacle which overshadows the visualization of the trailer as an artistic object, is superimposed by the multiple rhetorical possibilities that enable the construction of an effective and creative tool for the cinematographic entertainment industry. To show the object as a genre, historical, typological, stylistic, copyright and marketing relationships related to the trailer are addressed, as well as its textual relations consolidated from analytical propositions.